2015
DOI: 10.1007/s00394-015-1019-6
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine supplementation does not enhance blood flow and muscle performance in healthy and physically active older women

Abstract: These results show that acute L-arg supplementation provides no ergogenic effect on blood flow and muscle performance in older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 64 publications
1
11
0
1
Order By: Relevance
“…For example, Greer and investigators [ 637 ] examined the ability of arginine + alpha-ketoglutarate and reported that the combination did not significantly impact muscle endurance and significantly reduced the number of chin-ups completed. Similar outcomes were found by Aguiar et al [ 638 ] in older women whereby arginine supplementation failed to impact muscle performance. Sunderland et al [ 639 ] supplemented 18 endurance-trained cyclists for 28 days with either arginine (12 g/day) or corn starch and concluded that arginine did not impact VO 2 Max or ventilatory threshold.…”
Section: Introductionsupporting
confidence: 87%
“…For example, Greer and investigators [ 637 ] examined the ability of arginine + alpha-ketoglutarate and reported that the combination did not significantly impact muscle endurance and significantly reduced the number of chin-ups completed. Similar outcomes were found by Aguiar et al [ 638 ] in older women whereby arginine supplementation failed to impact muscle performance. Sunderland et al [ 639 ] supplemented 18 endurance-trained cyclists for 28 days with either arginine (12 g/day) or corn starch and concluded that arginine did not impact VO 2 Max or ventilatory threshold.…”
Section: Introductionsupporting
confidence: 87%
“…First, L-arg supplementation may be ineffective to increase NO production and, consequently, muscle blood flow at rest and exercise conditions in healthy individuals. This hypothesis is supported by several studies involving healthy individuals that showed no additional effect of Larg supplementation (range: 6 -10 g) on NO production (measured by NO 2 and NO 3 -) (Blum et al 2000;Evans et al 2004;2012a;Liu et al 2009;Koppo et al 2009;Tang et al 2011) and blood flow (Blum et al 2000;Tang et al 2011;Aguiar et al 2016), despite increases in plasma L-arg concentration (Blum et al 2000;Evans et al 2004;Liu et al 2009;Tang et al 2011;2012a). This is consistent with fact that physiological concentrations of Larg (range: 40 to 100 µmol•L -1 ) in healthy individuals are sufficient to saturate endothelial nitric oxide synthase, which is ∼2-20 µmol•L -1 (Durante et al 2007), resulting in no additional effect on NO production.…”
Section: Discussionmentioning
confidence: 75%
“…When ADMA levels are low, eNOS flux is near the V max at physiologic arginine levels . Consequently, clinical studies of l _arginine in healthy individuals generally fail to show beneficial effects on blood flow . Similarly, clinical trials using l _arginine in primary RP consistently demonstrate no appreciable effect .…”
Section: Effects Of Adma In Raynaud's Phenomenon and L_arginine Treatmentioning
confidence: 99%
“…61 Consequently, clinical studies of L-arginine in healthy individuals generally fail to show beneficial effects on blood flow. 34,[62][63][64][65] Similarly, clinical trials using L-arginine in primary RP consistently demonstrate no appreciable effect. 66,67 Whether or not there is a long-term protective effect of arginine supplementation in these patients is speculative and beyond the scope of this article.…”
Section: Effects Of Adma In Raynaud's Phenomenon and L-arginine Treatmentioning
confidence: 99%